Hydrazonoyl Halides as Precursors for Synthesis of Bioactive Thiazole and Thiadiazole Derivatives: Synthesis, Molecular Docking and Pharmacological Study - A. Farghaly, Thoraya; M. Gomha, Sobhi; R. Sayed, Abdelwahed; A. Khedr, Mohammed (Current Organic Synthesis, 2016)
New thiazole and 1,3,4-thiadiazole derivatives were synthesized from the reaction of hydrazonoyl halides and each of 3-(4-fluorophenyl)-3,4,5,6-tetrahydrobenzo[6,7]cyclohepta[1,2-c]pyrazole-2(1H)-carbothioamide and (E)-3-[mercapto(phenylamino)methylene]-thiochroman-4-one, respectively. The structures of all the newly synthesized compounds were established by elemental and spectral analyses. All of the synthesized compounds were tested for anticancer activity against colon cancer cell line HT29, human breast cancer cells MCF-7 and human hepatocellular carcinoma cell line HepG2. Many derivatives of the tested compounds showed moderate to high anticancer activity. Also, molecular docking against HER2 kinase domain revealed high free binding energy and good binding mode. The structure activity relationship (SAR) of tested compounds was studied.
Keywords: benzosuberone